Townspeople and peasants in social structure Starodub regiment (1654–1781) - Khrolenok, Evgeniy V. (Journal of the Belarusian State University. History, 2021)
The territory of the Starodub regiment is unique in historical terms. Being the center of the region of the Grand Duchy of Lithuania, it was one of its lands able to gain a foothold in the Getman Ukraine. At the same time, Starodubshchina is now the only part of the Hetman region that is part of the Russian Federation. Thus, the region has incorporated traditions, culture and legal customs of all three states, on the border of which it is now located. Despite the considerable interest in the history of the Starodub regiment as a whole, the social history of ordinary rural and urban residents remains poorly understood. The aim of this work is an attempt to illuminate the social situation of the pospolits: townspeople and peasants of the Starodubsky regiment from the moment the Cossack administration was established in the region in 1654 until the population of the region was subordinated to general imperial Russian standards. And also to reveal the characteristic differences of this region. The article was created on the basis of the analysis of various, including little-studied documents stored in the archives of Belarus, Ukraine and Russia, as well as the works of Russian and Ukrainian scientists. The process of establishing city self-government in Starodub and the formation in its midst of a unique elite – noble bourgeois is shown. Many representatives of this social group went through the process of evolution from urban dwellers to Cossack foreman and the subsequent Russian nobility over the indicated period. In addition, the social status of rural residents of the Starodub regiment is described. Which with the establishment of the Cossack administration received personal freedom, but by the end of the 18th century completely lost her. The examples of residents of specific settlements show the methods that the peasants resorted to trying to avoid dependence on large landowners, as well as the process of distinguishing between the pospolits and the Cossack class. At the same time, emphasis was placed on the characteristic differences in the social status of urban and rural residents of the Starodub regiment from other lands that were part of the Russian Empire. The totality of the facts revealed in this way reinforces the main thesis about the complexity and versatility of this Belarusian-Russian-Ukrainian region.
Keywords: Starodub; townspeople; peasants; pospolits; Hetmanate; Starodub regiment; social evolution